2016
DOI: 10.1007/s11426-016-5583-2
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic study of binary mixtures between pyrrolidinium bis(triflorosulfonyl)imide and dimethyl sulfoxide/acetonitrile

Abstract: Molecular interactions of a representative pyrrolidinium-based ionic liquid 1-butyl-1-methyl-pyrrolidinium bis(triflorosulfonyl)-imide ([BMPyrr][TFSI]) with dimethyl sulfoxide (DMSO) and acetonitrile (AN) have been analyzed in this work. Attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) and density functional theory (DFT) calculations are used in the investigation, while excess infrared spectra and two-dimensional correlation spectroscopy are used to explore the data in detail. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…[17,18] Again, the acidityd etermined is an averagep roperty of the bulk solutions. In the present work, we found that the excess spectrao ft he CNs tretching vibration could provide information on the microenvironments of solutions, [23,24] owing to the spectralresolution enhancement of excess spectroscopy, [25][26][27][28] ac oncept proposed in our laboratory. [19][20][21][22] Pelmenschikov et al, [19] used CD 3 CN as ap robe of Lewis and Brønsted acidityt od istinguish different adsorbing sites of zeolites.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[17,18] Again, the acidityd etermined is an averagep roperty of the bulk solutions. In the present work, we found that the excess spectrao ft he CNs tretching vibration could provide information on the microenvironments of solutions, [23,24] owing to the spectralresolution enhancement of excess spectroscopy, [25][26][27][28] ac oncept proposed in our laboratory. [19][20][21][22] Pelmenschikov et al, [19] used CD 3 CN as ap robe of Lewis and Brønsted acidityt od istinguish different adsorbing sites of zeolites.…”
Section: Introductionmentioning
confidence: 92%
“…Gai et al [21] introduced CNg roup into biological systems to detect changes on the local electrostatic fields of proteins. In the present work, we found that the excess spectrao ft he CNs tretching vibration could provide information on the microenvironments of solutions, [23,24] owing to the spectralresolution enhancement of excess spectroscopy, [25][26][27][28] ac oncept proposed in our laboratory.…”
Section: Introductionmentioning
confidence: 92%
“…Besides, the positive peaks appearing at higher wavenumbers and the negative peaks appearing at lower wavenumbers can explain the blue shifts of ν(S=O) and ν(C−F) in Figure S2. According to literature, [23] the blue shifts mean that H‐bonding interactions involving S=O and C−F are getting stronger upon dilution. It is also found that the intensity of both positive and negative peaks increases with the addition of CD 3 CN until x (CD 3 CN)=0.6 and then decreases.…”
Section: Resultsmentioning
confidence: 83%
“…In another word, H-bonding interactions between CD 3 CN and [TFSI] À anion are stronger than those CD 3 CNÀ CD 3 CN interactions. [23] It can be seen from Figure 2(c) that with the increasing mole fraction of CD 3 CN, absorption peaks of ν as, i.p. (S=O), ν as, o.p.…”
Section: Analysis Of ν(C�n) ν(Cà D) ν(S=o) and ν(Cà F)mentioning
confidence: 93%
“…46 FTIR of OMSCF-400 confirms the presence of the SO bond, which is not found in MSCF (Figure S3). 49 These results indicate the successful incorporation of oxygen into MoS 2 .…”
Section: Resultsmentioning
confidence: 96%